2013
DOI: 10.2217/bmm.13.11
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nasal Nitric Oxide During Humming: Potential Clinical Tool in Sinonasal Disease?

Abstract: The use of nasal nitric oxide (nNO) in sinonasal disease has recently been advocated as a potential tool to explore upper inflammatory airway disease. However, it is currently hampered by some factors including the wide range of measurement methods, the presence of various confounding factors and the heterogeneity of the study population. The contribution of nasal airway and paranasal sinuses communicating with the nose through the ostia represents the main confounding factor. There is accumulating evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…In previous studies, it has been shown that humming can release nitric oxide from the paranasal sinuses during exhalation. (14) Therefore, we studied sinus ventilation during humming and, as seen from Figure 2C, the maxillary sinuses are displayed on the anterior gamma camera images, confirming efficient sinus ventilation.…”
Section: Development Of the Pulsating Airflow Technique For Sinus Drumentioning
confidence: 59%
See 2 more Smart Citations
“…In previous studies, it has been shown that humming can release nitric oxide from the paranasal sinuses during exhalation. (14) Therefore, we studied sinus ventilation during humming and, as seen from Figure 2C, the maxillary sinuses are displayed on the anterior gamma camera images, confirming efficient sinus ventilation.…”
Section: Development Of the Pulsating Airflow Technique For Sinus Drumentioning
confidence: 59%
“…Ventilation and sinus drug delivery was also confirmed in studies by Maniscalco et al (12,14) In these studies, oscillatory airflow was induced during humming, and they could show release of nitric oxide from the sinuses and its suppression by inhalation of the nitric oxide synthase inhibitor L-NAME. But these studies require nasal inhalation, because humming can only be performed during exhalation.…”
Section: Opportunities For the Aerosol Treatment Of Nasal Disordersmentioning
confidence: 70%
See 1 more Smart Citation
“…The sinuses, which contain a very high NO concentration [21], communicate with the nasal cavity through ostia, and there is a continuous NO gas exchange between these cavities [22]. Therefore, the possibility to detect alterations in nasal NO output is limited by the high background NO levels present in paranasal sinuses, which could easily blunt slight alteration of NO [23]. Moreover, the limited number of patients with sinusitis enrolled in our study may have influenced the statistical significance.…”
mentioning
confidence: 95%
“…In addition to the above-cited studies linking radiographic and/or endoscopic OMC obstruction to a blunted nNO response to humming, this transient response has been shown to be normalize after effective medical therapy of nasal polyposis, consistent with restoration of OMC patency [34]. As noted above, however, in our earlier study of normal controls and allergic rhinitics without sinusitis, the magnitude of the humming-induced nNO transient did not correlate with radiographically-documented OMC cross-sectional area, leading one observer to characterize its blunting as a high-threshold, "all or none" response [31,35]. Given these uncertainties, along with the variability inherent in the humming maneuver, future clinical validation studies, in addition to including multiple clinical sub-groups to maximize external validity, might profitably examine whether the nNO response to external acoustic stimulation yields more clinically-coherent results than does the response to humming.…”
Section: Discussionmentioning
confidence: 71%